Implementasi Pengelolaan Pariwisata Berkelanjutan Di Kota Semarang - Siauw Tiffani Setiono; Teuku Afrizal; Eko Supriyono; Rinaldy May Wendra; Annisa Nurfitriani (Universitas Medan Area, 2021)
Tourism is one of the fields that can increase local revenue. Semarang City, has an old city icon that can be a strong attraction for the tourism aspect. The research aims to determine tourism development plans and programs, the involvement of organizations and other relevant parties, the mechanism of implementing tourism development, and the pattern of supervision carried out for sustainable tourism development. This pattern of sustainable tourism development has high hopes for the preservation of the environment. In its implementation, it replicates the Pentahelix model, which involves Government, Private, Community, Academic and mass media components. Thus the management of tourism in the city of Semarang is the responsibility of all stakeholders. So that tourism destinations that can support regional and central income without ignoring the environment. Recommendations that can be proposed are Optimizing the potential of natural and cultural tourism as regional tourism icons; Sustainable tourism development needs to be done by empowering local communities.